The Effects of University Education on the Political Attitudes of Young Adults - Mintz, Eric (Canadian Journal of Higher Education, 1998)
The attitudes of a panel of young adults in the Corner Brook, Newfoundland area on a variety of politically-relevant topics were examined over a two year period to measure the possible effects of a university education. Generally, those who attended university did not change significantly in their attitudes as compared to high school graduates who did not attend university.